Research on Consumer Behavior and Optimization Strategies in the Cultural and Creative Products Market - Xia, Yujing; Liu, Jiaxuan (Journal of Global Economy, Business and Finance, 2025)
In the economic development, the cultural industry occupies an important position. As cultural and creative products gain increasing attention and popularity, they have also become a window for showcasing China’s cultural soft power. This paper comprehensively adopts methods such as questionnaire surveys and in-depth interviews to conduct an in-depth analysis of consumer behavior in the cultural and creative market and puts forward targeted strategic suggestions. The study finds that consumers of cultural and creative products are characterized by a younger age and a higher proportion of females. Most of them have a price acceptance range of 80-150 yuan, and they prefer products that combine practicality with artistic appeal and have the attribute of tourist souvenirs. Moreover, young consumers attach importance to the social sharing value of products. However, the current market faces problems such as mismatches between product positioning and consumer structure, unbalanced pricing strategies, lack of precision in marketing, and product innovation that fails to align with consumer expectations. Therefore, based on the analysis results of the binary Logistic model and other methods, this study starts with marketing strategies and proposes suggestions including precise product development, optimization of the pricing system, implementation of precision marketing, and product innovation centered on consumer needs. These measures aim to promote the development of cultural and creative industry and contribute to cultural inheritance and economic growth.